Metal–organic framework derived hierarchical copper cobalt sulfide nanosheet arrays for high-performance solid-state asymmetric supercapacitors. Issue 14 (22nd March 2019) - Bahaa, Ahmed; Balamurugan, Jayaraman; Kim, Nam Hoon; Lee, Joong Hee
Abstract : A novel strategy is proposed to design and fabricate hierarchical CuCo2 S4 nanosheet arrays from a metal–organic framework for high-performance solid-state supercapacitors. Abstract : Metal–organic framework derived nanostructures have unique properties, such as large specific surface area, exclusive porous networks, numerous active sites, and exceptional electrochemical properties, when compared to traditional nanostructures. Herein, a novel strategy is proposed to design and fabricate hierarchical copper cobalt sulfide nanosheet (CuCo2 S4 NS) arrays from a metal–organic framework. The hierarchical CuCo2 S4 NS arrays can provide enriched electroactive sites, as well as shorten the ion/electron diffusion pathways. When evaluated as electrodes for supercapacitors (SCs), the CuCo2 S4 NS electrode exhibited remarkable electrochemical properties with an ultra-high specific capacity of ∼409.2 mA h g −1 and an areal capacity of ∼0.96 mA h cm −2 at a current density of 3 mA cm −2, exceptional rate capability (∼77.9% capacity retention at a higher current density of 50 mA cm −2 ), and outstanding cycling stability (∼94.2% capacity retention after 10 000 cycles). Most importantly, the assembled CuCo2 S4 NS//Fe2 O3 /NG solid-state asymmetric SC displayed a wide operating potential window of 1.6 V with an ultra-high volumetric capacity of ∼2.1 mA h cm −3 at a current density of 3 mA cm −2, an excellent energy density of ∼89.6 W h kg −1 at a power density of ∼663 W kg −1, and an ultra-long cycle life (∼91.5% capacity retention after 10 000 cycles). This proposed method provides a general protocol to design and fabricate metal sulfide nanosheet arrays with superior electrochemical energy storage properties and exceptional cycling stability, holding limitless potential for future energy storage devices in commercial aspects.